The Moon is Down Movie Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
Four men from left to right: German soldier extra, Doctor Albert Winter (Lee Cobb), George Corell (E. J. Ballantine), Mayor Orden (Henry Travers) at the gallows. RESTRICTED USE